AL-SUNNAH DAN TAFSIR ALQURAN (Tinjauan tentang Fungsi dan Posisi al-Sunnah dalam Tafsir Alquran) - Mustopa Mustopa (UIN Siber Syekh Nurjati Cirebon, 2017)
The companions when the Messenger of Allah. still alive, if they find a problem related to the Qur'an they ask directly to the Messenger of Allah, then the Prophet. explain it to them. The position of the Prophet in this case as an explanation of the Qur'an and this position is the position and function of al-Sunnah in the interpretation of the Qur'an. There are several opinions of the scholars regarding the interpretation of the Prophet. against the Koran. First, the Messenger of Allah. explain the content of the Koran to his friends. As Ibn Taymiyah said that the Messenger of Allah. obligatory to teach the content of the Koran to his friends. Secondly, the Messenger of Allah. just a little in explaining to his friends. As is the story of 'A'ishah, the Messenger of Allah. do not interpret even one verse of the Koran except very limited in accordance with what is taught by the angel Gabriel.